A culture-based development of mathematics learning: A case on the Muhammad Cheng Hoo Mosque of Surabaya - Nur Fadilatul Ilmiyah; Zulinda Nur Sa’idah; Ifatun Nisa'; Ika Kusuma Wijaya (Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
Learning mathematics in schools aim to make students able to make mathematics as a solution or approach in simplifying or solving daily problems. To achieve this goal, it is necessary to have a culture-based mathematics learning which expected to be able to help students understand and master mathematics better. The purpose of this study is to identify the mathematical elements contained in the ornament and architecture of the Muhammad Cheng Hoo Mosque in Surabaya. This research is qualitative research with an ethnographic approach. Data collected by using a literature study, observation, documentation, and interviews. Data analysis is classified into several stages, namely domain and taxonomic analysis, componential analysis, and cultural theme analysis. The results showed that there are mathematical elements in the ornament and architecture of the Muhammad Cheng Hoo Mosque in Surabaya included the concepts of plane geometry, solid geometry, and transformational geometry. Mathematical elements in this mosque may be used as material for the development of culture-based mathematics learning at the primary and secondary school levels.